Dye characterisation of Tahitian plants and molecular identification of mati red in historical barkcloth - Diego Tamburini (Scientific Reports)
Abstract Various natural dye sources have been historically used and are still used today to decorate Pacific barkcloth. The identification of these natural dyes is a challenging task due to their molecular complexity and the scarcity of scientific investigations. In this study, barkcloth samples collected in Tahiti and dyed using local plants, including fruits of Thespesia populnea (L.) Sol. ex Corrêa, leaves of Cordia subcordata Lam., fruits of Ficus tinctoria G.Forst. and flower stalks of Musa troglodytarum L., were analysed by high-performance liquid chromatography coupled to diode array detector and mass spectrometry (HPLC–DAD–MS). The combination of extracts from the leaves of C. subcordata Lam. and fruits of F. tinctoria G.Forst. represents a Tahitian recipe to produce mati dye, which has never been analysed so far nor identified in historic barkcloth, despite being mentioned in historical accounts. The complex analytical results enabled molecular markers to be annotated in all samples. Gossypol and its derivatives are the main components of the dye from T. populnea (L.) Sol. ex Corrêa. Various anthocyanin O-glycosides, flavonoid C-glycosides as well as phenolic compounds are present in mati dye alongside condensed tannins. Anthocyanin O-hexoside-deoxyhexosides and polyacetylated O-p-coumaroylsucrose esters are found in the dye from M. troglodytarum L. These results constitute a precious molecular database and prompted a re-evaluation of the findings of a previous analytical study on samples from the Tahitian mourner’s costume in the British Museum collection. The new analytical evidence enabled mati dye to be identified in most red areas of the costume, correcting previous interpretations and providing the first scientific confirmation of the use of this dye in historical context. This study enhances the possibility of identifying traditional dye sources in historic artefacts from the Pacific islands and emphasises the benefits of sharing and exchanging knowledge with local communities.